Analisis Potensi Batuan Reservoir pada Cekungan Biliton Berdasarkan Data Well Logging untuk Eksplorasi Hidrokarbon - Utami, Prapti Abdi Fina; Fazera, Asha Asfaninda Firda; Silaban, Emilya; Purniawan, Eka Maulividia Prilianti; Christhy, Michelle Ananta; Badaruddin, Dzul Fadli (GEOSAINS KUTAI BASIN, 2024)
The Biliton Basin in the western Java Sea, part of the southeastern margin of the Sunda Craton, shows potential for hydrocarbons based on well logging analyses from the Sari-1, Nila-1, and Parang wells. Formed during the Eocene-Oligocene extension, this basin's stratigraphy includes the Jatibarang and Banuwati formations. Well logging data identified the Air Benakat and Talang Akar formations as primary reservoir rocks with high porosity. However, only the Parang well displayed indications of oil at certain depths. While the Sari-1 and Nila-1 wells also have reservoir potential, they did not show the presence of hydrocarbons. This study underscores the existence of potential reservoir and seal rocks in the Biliton Basin, but significant hydrocarbon reserves have yet to be discovered. Further exploration is necessary to evaluate the hydrocarbon potential in this region.Keywords: Biliton Basin, hydrocarbons, well logging, Sunda Craton.